Colonial breeding impacts potentially fitness-relevant cognitive processes in barn swallows - Angela Medina-García; Ellen Scherner; Molly T. McDermott; Mark E. Hauber; Rebecca J. Safran (Animal Cognition)
Abstract Many animals breed colonially, often in dense clusters, representing a complex social environment with cognitive demands that could ultimately impact individual fitness. However, the effects of social breeding on the evolution of cognitive processes remain largely unknown. We tested the hypothesis that facultative colonial breeding influences attention and decision-making. Barn swallows (Hirundo rustica) breed in solitary pairs or in a range of colony sizes, up to dozens of pairs. We tested for selective attention to social information with playbacks of conspecific alarm calls and for decision-making with simulated predator intrusions, across a range of colony sizes from 1 to 33 pairs. We also evaluated the adaptive value of both processes by measuring seasonal reproductive success. Swallows breeding in larger colonies were more selective in their attention to social information. Birds breeding in larger colonies were also less risk averse, deciding to return more quickly to their nests after a predator approach paradigm. Finally, birds that showed higher selective attention hatched more eggs and birds that returned to their nests more quickly after a predator intrusion had more nestlings. Although we cannot fully attribute these fitness outcomes to the cognitive measures considered in this study, our results suggest that social breeding plays a role in adaptively shaping both the acquisition of social information and decision-making.